(untitled) (XXI Century. Spanish Literature and Culture, 2024)
The present article provides an analysis of Carmen (2002) by Lourdes Ortiz, a re-evaluation of the novel Carmen (1845) by Prosper Mérimée and the opera Carmen (1875) by Georges Bizet. Through a brief and unique act, Ortiz’s Carmen, a victim of an abuser, leads us to a methodical inquiry into the normalized behaviors in a misogynistic and sexist society. Carmen responds to this oppression with a revolutionary discourse, seeking to free herself from the social structure that attempts to oppress her. Denunciation and liberation are manifested in the offering of her body in a suicidal act as a sacrifice. The investigation will be conducted from a semiotic basis starting from the original texts to outline the reinterpretation of the character from Ortiz’s gender perspective.